G3BPs in Plant Stress - Abulfaraj, Aala A.; Hirt, Heribert; Rayapuram, Naganand (Frontiers in Plant Science, 2021)
The sessile nature of plants enforces highly adaptable strategies to adapt to different environmental stresses. Plants respond to these stresses by a massive reprogramming of mRNA metabolism. Balancing of mRNA fates, including translation, sequestration, and decay is essential for plants to not only coordinate growth and development but also to combat biotic and abiotic environmental stresses. RNA stress granules (SGs) and processing bodies (P bodies) synchronize mRNA metabolism for optimum functioning of an organism. SGs are evolutionarily conserved cytoplasmic localized RNA-protein storage sites that are formed in response to adverse conditions, harboring mostly but not always translationally inactive mRNAs. SGs disassemble and release mRNAs into a translationally active form upon stress relief. RasGAP SH3 domain binding proteins (G3BPs or Rasputins) are “scaffolds” for the assembly and stability of SGs, which coordinate receptor mediated signal transduction with RNA metabolism. The role of G3BPs in the formation of SGs is well established in mammals, but G3BPs in plants are poorly characterized. In this review, we discuss recent findings of the dynamics and functions of plant G3BPs in response to environmental stresses and speculate on possible mechanisms such as transcription and post-translational modifications that might regulate the function of this important family of proteins.